RANCANG BANGUN SISTEM INFORMASI PENEMPATAN AREA KERJA CLEANING SERVICE UNTUK MENINGKATKAN PELAYANAN BANDARA - Euis Sitinur Aisyah; Bayu Pramono; Haris Munandar (UNIVERSITAS RAHARJA, 2019)
The airport is one of the entry gates of a country, in the airport there are many work divisions that support and facilitate all existing activities, one of which is a cleaning service that has a large enough function that is to improve cleanliness and comfort in the airport area, cleaning services that exist when This is managed by the company and works with companies that focus on cleaning service in each terminal. The placement of the cleaning service area is still manual and takes a lot of time and involves several parts in the process, and inhibits in terms of time in the process of cleaning the area at the airport so that it can reduce the quality of services that have an inconvenience, to overcome the problem. which is currently running to find out the components of the problem that exist. The results to be achieved in this study is the application of a system that facilitates the process, namely by making an information system placement of web-based cleaning service work areas that is used as a reference in the system development process later. The analytical method used in this study uses the PIECES method, to assist in the process of analyzing the system that has been running. The Programming Language used in building this system uses PHP, MySQL as a database to store master data, transactions and users.